The Comperatıvely Evaluatıon Of The Nonsurgıcal Orthodontıc Treatment Results Of Severe Skeletal Class Iıı Total Openbıte Cases: Case Reports - Meliha Rübendüz (Galenos Yayinevi, 2001)
The aim of this study is to present the treatment progress and results of two skeletal Class III total openbite cases who are in different growth stages and have different intermaxillary relationships. The first case is a boy in post-pubertal stage and has a skeletal and dental Class III malocclusion with a long faced appereance. The second case is a young adult girl having a skeletal Class III openbite pattern and dental Class II division I openbite malocclusion. Fixed mechanics followed functional orthopedic treatment in the first case. The second case was treated only by fixed mechanics. In both of the cases four first molars were extracted because of excessive crown destructions and dental Class I occlusion with normal overbite and overjet relationships was achieved. In addition, acceptable esthetic results in the skeletal and soft-tissue structures were obtained. Normal dentofacial appereance was attained by the means of orthopedic treatment in the first non-adult case. While in the adult case, besides dental movements, the mandibular anterior autorotation due to the mesialization of the second molar was effective in the treatment results.